From Risk Neutral to Risk Taker: A Case Study of Credit Risk Deterioration in Indonesian Regional Development Bank - Thiar Cnur; Herdyana; Hari Gursida (International Journal Administration, Business & Organization, 2026)
Regional development banks in Indonesia face increasing pressure to balance credit expansion and risk management. This study investigates the dynamics of credit risk deterioration and risk preference shifts at Bank BJB Bogor Branch during the 2020-2024 period. A qualitative descriptive approach with a case study strategy was employed, complemented by quantitative descriptive analysis. Data were collected through in-depth interviews with branch managers, credit analysts, and risk management officers, supported by internal financial reports, OJK publications, and relevant banking regulations. Risk preference was measured using the Risk Preference Index, Loan-to-Deposit Ratio, and Credit Expansion Rate, while credit risk was assessed through Non-Performing Loan ratios and Capital Adequacy Ratio. The results reveal three critical findings. First, the branch experienced a significant risk preference shift from risk neutral to risk taker category driven by aggressive credit expansion alongside declining third-party funds. Second, the MSME credit segment suffered catastrophic quality deterioration reaching an alarming non-performing level in the final observation year. Third, a structural funding vulnerability was identified as regional government deposits declined dramatically, forcing the Loan-to-Deposit Ratio to exceed the optimal threshold. The study concludes that high capital adequacy alone is insufficient to contain credit risk when aggressive expansion into high-risk segments is unsupported by proportional risk management capacity and disciplined post-disbursement monitoring.